Trends in Antidepressant Use and Expenditure in Six Major Cities in China From 2013 to 2018 - Yu, Zhenwei; Zhang, Jianying; Zheng, Ying; Yu, Lingyan (Frontiers in Psychiatry, 2020)
The objective of this study was to investigate the current status and trends in antidepressant use and expenditure in China from 2013 to 2018. The study had a retrospective design based on prescribing data on antidepressant drugs, which was sourced from the Hospital Prescription Analysis Cooperative Project. The trends in hospital visits and corresponding expenditure on antidepressant drugs were examined. Subgroup analyses were carried out by sex, age, and drug class. A total of 1,795,230 outpatient prescriptions were collected from 79 hospitals in six major cities in China. Hospital visits with antidepressant prescriptions rose significantly from 244,626 in 2013 to 348,718 in 2018, reflecting a 42.6% increase (P < 0.05). The antidepressant expenditure also rose, increasing from 48.0 million Chinese yuan in 2013 to 64.8 million Chinese yuan in 2018. Compared with antidepressant prescriptions for men, there were approximately 1.6 times more antidepressant prescriptions written for women. The most frequent age category for antidepressant prescriptions was 45–64 years. The most commonly prescribed antidepressants were selective serotonin reuptake inhibitors (N06AB) and other antidepressants (N06AX), whereas tricyclic antidepressants (N06AA) accounted for only a small part of total antidepressant prescriptions. Flupentixol/melitracen and escitalopram were the most frequently prescribed antidepressants. Antidepressant prescribing rates continue to increase in China, although the prescribing patterns have changed over the past few years. The wide use of expensive antidepressants and those with weak clinical evidence raises concerns regarding the rational use of antidepressants. This study provides a basis for future stewardship by the government and medical institutions.